Use the graph of f(x) below to answer the following questions: \lim _{x \rightarrow-3^{-}} f(x)=\longrightarrow \lim _{x \rightarrow-3^{+}} f(x)=\longrightarrow \quad \lim _{x \rightarrow-3} f(x)=\square \quad f(-3)= \lim _{x \rightarrow-1^{-}} f(x)=\ldots \lim _{x \rightarrow-1^{+}} f(x)=\ldots \quad \lim _{x \rightarrow-1} f(x)=\longrightarrow(-1)= \lim _{x \rightarrow 4^{-}} f(x)=\longrightarrow \lim _{x \rightarrow 4^{+}} f(x)=\longrightarrow \quad \lim _{x \rightarrow 4} f(x)=\square \quad f(4)= \lim _{x \rightarrow 2^{-}} f(x)=\longrightarrow \lim _{x \rightarrow 2^{+}} f(x)=\longrightarrow \quad \lim _{x \rightarrow 2} f(x)=\square \quad f(2)=

Fig: 1

Fig: 2

Fig: 3

Fig: 4

Fig: 5

Success

Verified